A positive aspect of man’s concious - Mirghani, Mohamed Elwathig Saeed; Jami, Mohammed Saedi (Sci.Int.(Lahore), 2014)
ABSTRACT - Being an honest perso means being polite to others and helping them. It looks simple, but being actually honest with others and with ourselves is not easy, it is a real challenge that requires hard work, serenity, patience and vigilance (watchfulness). This work tries to explain what dishonesty is and understand the workings of dishonesty. Then tries to explain how to practice to be honest in everything as way of life; nothing is as liberating (beneficial) as having nothing to hide, at the same time, keeping a balance between disclosure and confidentiality. The paper will also throw examples of daily practice in the form of questions for the reader to find out, which behavior is honest and how someone comes clean. As a conclusion; being honest is an ongoing process that will both challenge and benefit one throughout life. According to the Holy Qura’an, Sunnah and Hadith; a good practitioner of Islam is also an honest person since his ultimate conscientiousness is to Allah (S.W.T.) and his utmost objective is the pleasure of Allah (The Creator).